ASPIRATION PNEUMONIA IN THE ELDERLY - Thế Hoàng, Ngô; Thanh Trúc, Nguyễn; Thảo My, Phùng; Thị Thanh Ngân, Huỳnh; Duy Cường, Nguyễn; Đình Thanh, Lê (Journal of Health and Aging, 2025)
The global population is aging rapidly, leading to an increase in the number of elderly individuals who are more vulnerable and require comprehensive healthcare services, including long-term care and skilled nursing facilities. In this context, aspiration pneumonia has become a significant concern due to its high incidence, mortality rate, and substantial financial burden, particularly among elderly patients requiring intensive care unit admission. Aspiration pneumonia is defined as a pulmonary infection resulting from the inhalation of food, liquid, saliva, or stomach contents into the lungs, often due to impaired swallowing or consciousness. Symptoms may include cough, fever, shortness of breath, chest pain, and fatigue . Risk factors include neurological disorders, impaired consciousness, advanced age, and conditions affecting swallowing. Diagnosis is based on clinical presentation, imaging studies such as chest X-rays or CT scans, and, if necessary, swallowing assessments. Treatment typically involves antibiotics, and in severe cases, may include oxygen therapy or mechanical ventilation . Preventive measures focus on managing risk factors, improving swallowing function, and maintaining oral hygiene. This article aims to provide information on aspiration pneumonia in the elderly, including its causes, symptoms, diagnosis, and treatment, to raise awareness and help reduce the incidence and mortality associated with this condition.